Urbanização e impactos socioambientais em áreas protegidas: o Estudo de Caso do Parque Ambiental Antônio Danúbio, Ananindeua-Pa - SARGES FILHO, Leudes (2025)
From the second half of the 20th century onwards, the urbanization process in underdeveloped countries underwent a significant and completely unregulated acceleration, accompanied by serious environmental issues. In Brazil, concern for environmental matters became more pronounced and positive with the promulgation of the Constitution of the Federative Republic of Brazil in 1988 and the enactment of laws related to the establishment of protected areas, such as the Antônio Danúbio Environmental Park in Ananindeua. The objective of this study is to identify and characterize the factors that cause socio-environmental impacts in urban protected areas, with a case study of the Environmental Park of Ananindeua-PA. To achieve this, the research is based on a bibliographic survey in official institutions to establish the chronology of the park's creation and implementation, along with the development of location and multitemporal maps. Additionally, the study includes the characterization of the urban and climatobotanical landscape of the area, the identification and analysis of environmental impacts resulting from the creation and implementation of the Metropolitan BRT system, as well as an assessment of municipal government accountability concerning abandonment, negligence, and omission, alongside an analysis of the role of other social actors involved in the process. The research highlighted the park’s importance for environmental conservation, ecological education, and public recreation, emphasizing its role in mitigating the urban heat island effect and maintaining urban biodiversity. It is concluded that effective public policies and investments in the park’s infrastructure are essential for its preservation and enhancement within the urban context of Ananindeua.